Biomechanics of movement in tennis - Roeter, E. P.; Ellenbecker, T. S. (coachesinfo.com)
The content of the report: - Introduction - Effects of Surface on Court Movement - Effect of Tennis Balls on Court Movement - Effect of Modern Technique on Court Movement - Characteristics of Court Movement - Mechanics of the Split Step - Mechanics of the Foot and Ankle During On-Court Movement